1978
DOI: 10.1002/zaac.19784390132
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der Hydrate des Na2PHO3, Phasenbeziehungen und kristallographische Untersuchungen

Abstract: Die Dehydratisierung von NaaPHO3 · 5 H2O zum wasserfreien Salz wurde mit Thermogravimetrie und Differentialthermoanalyse untersucht. Die Entwässerung verläuft über die Stufe eines intermediären niederen Hydrates, Na2PHO3 · 0,5 H2O. Einkristalle des Hemihydrates konnten aus Lösung gezüchtet werden; es kristallisiert rhomboedrisch, Raumgruppe R32, R3m oder R3m, mit a = 18,918(5) ß und α = 33,00(2)°. – Die Kristallstruktur von Na2PHO3 · 5 H2O wurde neu bestimmt. Das Pentahydrat kristallisiert orthorhombisch, Raum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1978
1978
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The average P-O distance, 1.52(2)/k, and the average O-P-O angle, 111 (3) °, also agree with literature data, e.g. for Na2HPO3.5H20 (Brodalla, Goeters, Kniep, Mootz & Wunderlich, 1978), CuHPO 3 . 2H20 (Handlovi6, 1969) or MgHPO 3.…”
supporting
confidence: 89%
“…The average P-O distance, 1.52(2)/k, and the average O-P-O angle, 111 (3) °, also agree with literature data, e.g. for Na2HPO3.5H20 (Brodalla, Goeters, Kniep, Mootz & Wunderlich, 1978), CuHPO 3 . 2H20 (Handlovi6, 1969) or MgHPO 3.…”
supporting
confidence: 89%
“…In the known phosphite structures, LiH2PO a (Philippot & Lindqvist, 1970, X-ray data; Johansson & Lindqvist, 1976, neutron data), Na2HPOa.5H20 (Brodalla, Goeters, Kniep, Mootz & Wunderlich, 1978), Na0.sH2.sPOa (Hazell, Hazell & Kratochvil, 1982), 2KH2PO3.H3PO3 (Loub & Paulus, 1981b), MgHPO 3. 6H20 (Corbridge, 1956), SnHPOa (McDonald & Eriks, 1980), Sb2(HPO3) 3 (Loub & Paulus, 1981a), MnHaP206.…”
mentioning
confidence: 99%
“…The crystal structure of disodium phosphonate pentahydrate with respect to the non-hydrogen atoms was determined in 1971 from single crystal data [1]. The positions of the Hatoms were refined later by Brodalla et al [6], who also found the second hydrate phase, Na 2 HPO 3 · 0.5H 2 O, of which the crystal structure is still unknown. For the anhydride, only unindexed powder diffraction data were published [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The positions of the Hatoms were refined later by Brodalla et al [6], who also found the second hydrate phase, Na 2 HPO 3 · 0.5H 2 O, of which the crystal structure is still unknown. For the anhydride, only unindexed powder diffraction data were published [6,7]. In this paper we report on the crystal structure determination of Na 2 HPO 3 using high resolution synchrotron powder diffraction.…”
Section: Introductionmentioning
confidence: 99%